PENGARUH PENGGUNAAN LIVIN' BY MANDIRI TERHADAP KEMUDAHAN LAYANAN KEUANGAN PADA MAHASISWA MANAJEMEN UNIVERSITAS NEGERI MEDAN ANGKATAN 2025 - Clara Citra Sinaga; Hawila Manik; Trizthan Irfan Hermawan; Kholillah Azahra Barus; Lasmini Manik; Namira Shafalda Prabudi; Nurul Wardani Lubis (CV. Lafadz Jaya, 2026)
The digital banking revolution has brought about fundamental changes in the way people access financial services, including amongst university students, a demographic group with a high rate of technology adoption. This study aims to analyse the impact of using the Livin’ by Mandiri app on the perceived ease of access to financial services among students on the Management Programme at the State University of Medan, intake year 2025. The study employs a quantitative approach using a survey design, involving 120 respondents selected through purposive sampling. Data collection was carried out using a five-point Likert scale questionnaire that had been tested for validity and reliability. The independent variables in this study included ease of use of the interface, system reliability, completeness of service features, and transaction security, whilst the dependent variable was the ease of financial services, measured based on user perceptions. Data analysis was performed using multiple linear regression with the aid of SPSS version 26 software. The results indicate that, taken together, all independent variables have a significant effect on the ease of financial services (F = 47.83; p < 0.01). When analysed individually, ease of use of the interface makes the largest contribution (β = 0.421; p < 0.01), followed by service feature completeness (β = 0.318; p < 0.01), transaction security (β = 0.276; p < 0.05), and system reliability (β = 0.201; p < 0.05). The coefficient of determination (R²) of 0.743 indicates that 74.3% of the variation in the ease of financial services can be explained by these four variables. The findings of this study have important implications for the development of digital banking services tailored to the needs of the student segment.